(untitled) (International Seven Journal of Multidisciplinary, 2022)
Effective administrative skills are essential for navigating the complexities of modern organizational environments. This article explores the development of three key competencies: business analysis, problem-solving, and critical thinking. It discusses how these interrelated skills contribute to strategic decision-making, operational efficiency, and organizational adaptability. Drawing on academic literature, the article highlights practical approaches to skill enhancement, such as experiential learning, data-driven training, and reflective practices. The integration of these competencies empowers professionals to make informed decisions, anticipate challenges, and drive continuous improvement within their organizations.